ABCA7 Regulates Brain Fatty Acid Metabolism During LPS-Induced Acute Inflammation - Aikawa, Tomonori; Ren, Yingxue; Holm, Marie-Louise; Asmann, Yan W.; Alam, Amer; Fitzgerald, Michael L.; Bu, Guojun; Kanekiyo, Takahisa (Frontiers in Neuroscience, 2021)
The ATP binding cassette subfamily A member 7 (ABCA7) gene is one of the significant susceptibility loci for Alzheimer’s disease (AD). Furthermore, ABCA7 loss of function variants resulted from premature termination codon in the gene are associated with increased risk for AD. ABCA7 belongs to the ABC transporter family, which mediates the transport of diverse metabolites across the cell membrane. ABCA7 is also involved in modulating immune responses. Because the immune system and lipid metabolism causatively engage in the pathogenesis of AD, we investigated how ABCA7 haplodeficiency modulates the metabolic profile in mouse brains during acute immune response using a metabolomics approach through LC/Q-TOF-MS. Peripheral lipopolysaccharide (LPS) stimulation substantially influenced the metabolite content in the cortex, however the effect on metabolic profiles in Abca7 heterozygous knockout mice (Abca7+/-) was modest compared to that in the control wild-type mice. Co-expression network analysis of the metabolomics dataset identified two modules significantly influenced by LPS administration and ABCA7 haplodeficiency, in which glycerophospholipid metabolism, linoleic acid metabolism, and α-linolenic acid metabolism were identified as major pathways. Consistent with these findings, we also found that LPS stimulation increased the brain levels of eicosapentaenoic acid, oleic acid, and palmitic acid in Abca7+/- mice, but not control mice. Together, our results indicate that ABCA7 is involved in the cross-talk between fatty acid metabolism and inflammation in the brain, and disturbances in these pathways may contribute to the risk for AD.